Gamified Recommendation Engines and their Role in Fostering Continuous Intention to Use Streaming Media Services - Prabhavathy, R.; Senthilkumar, S. (International Review of Management and Marketing, 2025)
This study investigates how users’ ongoing intentions to interact with over-the-top (OTT) streaming media services are improved by gamified recommendation engines. Users of streaming media services who had dealt with gamified recommendation algorithms were given a quantitative survey to complete. A strong direct effect (R2 = 0.864) of Gamification-Recommendation Engine Usage (GREU) on user engagement makes it an effective predictor. Intrinsic Motivation (IM) has a moderately positive effect on Continuance Intention towards Streaming Media (CISM), while Extrinsic Motivation (EM) has a negative effect on (CISM), which shows that excessive external benefits might not be helpful. GREU has significant impacts on both IM and EM, which makes its effect on driving factors stronger. The study lacks a longitudinal technique; therefore, it cannot determine variable relationships or user behaviour progression. The study only examines streaming media platforms and no other digital service sectors that use gamification and recommendation systems. AI-powered gamified recommendation systems and experience-oriented incentives (e.g., exclusive material, milestone achievements) can boost user retention through personalised playlists, narrative features, and interactive tools. This study highlights the special relationship between gamification, motivation, and consistent use of streaming services, adding to the expanding body of research on gamification and digital media engagement.